Geochemistry and Mixing Drive the Spatial Distribution of Free-Living Archaea and Bacteria in Yellowstone Lake - Kan, Jinjun; Clingenpeel, Scott; Dow, Charles L.; McDermott, Timothy R.; Macur, Richard E.; Inskeep, William P.; Nealson, Kenneth H. (Frontiers in Microbiology, 2016)
Yellowstone Lake, the largest subalpine lake in the United States, harbors great novelty and diversity of Bacteria and Archaea. Size-fractionated water samples (0.1-0.8 µm, 0.8-3.0 µm, and 3.0-20 µm) were collected from surface photic zone, deep mixing zone, and vent fluids at different locations in the lake by using a remotely operated vehicle (ROV). Quantification with real-time PCR indicated that Bacteria dominated free-living microorganisms with Bacteria/Archaea ratios ranging from 4037:1 (surface water) to 25:1 (vent water). Microbial population structures (both Bacteria and Archaea) were assessed using 454-FLX sequencing with a total of 662,302 pyrosequencing reads for V1 & V2 regions of 16S rRNA genes. Nonmetric multidimensional scaling (NMDS) analyses indicated that strong spatial distribution patterns existed from surface to deep vents for free-living Archaea and Bacteria in the Lake. Along with pH, major vent-associated geochemical constituents including CH4, CO2, H2, DIC (dissolved inorganic carbon), DOC (dissolved organic carbon), SO42-, O2 and metals were likely the major drivers for microbial population structures, however mixing events occurring in the lake also impacted the distribution patterns. Distinct Bacteria and Archaea were present among size fractions, and bigger size fractions included particle-associated microbes (>3 µm) and contained higher predicted OTU richness and microbial diversities (genus level) than free-living ones (< 0.8 µm). Our study represents the first attempt at addressing the spatial distribution of Bacteria and Archaea in Yellowstone Lake, and our results highlight the variable contribution of Archaea and Bacteria to the hydrogeochemical-relevant metabolism of hydrogen, carbon, nitrogen, and sulfur.